Prehistoric Settlement and Landscape Development in the Sandhill Belt of Southern Thy - Liversage, David; Robinson, David (Journal of Danish Archaeology, 1993)
Prehistoric Settlement and Landscape Development in the Sandhill Belt of Southern Thy